2022
DOI: 10.3390/molecules27134260
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Inflammatory Activity of Essential Oil from Zingiber ottensii Valeton in Animal Models

Abstract: Zingiber ottensii (ZO) Valeton, a local plant in Northern Thailand, has been widely used in traditional medicine. Many studies using in vitro models reveal its pharmacological activities, including the anti-inflammatory activity of ZO essential oil, extracted from ZO rhizomes. However, the scientific report to confirm its anti-inflammatory activity using animal models is still lacking. The present study aimed to evaluate the anti-inflammatory activity and explore the possible mechanisms of action of ZO essenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…49 By evaluating the anti-inflammatory activity of Zingiber ottensii (ZO) essential oil in rats, it was found that its possible mechanism was to inhibit TNF-α expression and inhibit COX-2 and PGE2 production. 50…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…49 By evaluating the anti-inflammatory activity of Zingiber ottensii (ZO) essential oil in rats, it was found that its possible mechanism was to inhibit TNF-α expression and inhibit COX-2 and PGE2 production. 50…”
Section: Resultsmentioning
confidence: 99%
“…49 By evaluating the anti-inflammatory activity of Zingiber ottensii (ZO) essential oil in rats, it was found that its possible mechanism was to inhibit TNF-α expression and inhibit COX-2 and PGE2 production. 50 Effect of SMEOs on acetic acid-induced peritoneal permeability increased inflammation in mice. In this experiment, the peritoneal permeability in mice was destroyed by acetic acid.…”
Section: Food and Function Papermentioning
confidence: 99%
“…NaIHS, by direct inhibition of COX‐2, may inhibit all of the above‐mentioned local inflammatory mediators: prostaglandins, 12 prostacyclins, 12 histamines, 38 bradykinins 6,33,39 and NO 31 and thus it may prevent vasodilation and pulmonary oedema. In the particular case of bradykinin, it is worth mentioning that NaIHS, through the aforementioned COX2‐dependent mechanism, may produce two effects: on the one hand, it may lead to down‐regulation of the bradykinin B2 receptor (B2R) 39 and on the other hand, it may promote ACE2 up‐regulation, as mentioned above 33 .…”
Section: Potential Therapeutic Effects Of Naihs In Pneumonia and Card...mentioning
confidence: 99%
“…IL‐8, 27 IL‐10, 27 IL‐18, 24 tumor necrosis factor‐alpha (TNF‐α), 13 interferon‐gamma (IFN‐γ), 13 transforming growth factor‐beta 1 (TGF‐β1), 13 intercellular adhesion molecule‐1 (ICAM‐1), 13 vascular adhesion molecule‐1 (VCAM‐1), 28 E‐selectin, 12 monocyte chemoattractant protein 1 (MCP‐1), 27 chemokine (C‐C motif) ligand 2 (CCL2), 27 growth factors granulocyte‐macrophage colony‐stimulating factor (GM‐CSF) 29 and hepatocyte growth factor (HGF) 27 ; (3) Down‐regulation of nitric oxide (NO) hyperproduction : see Table 3; (4) Inhibition of the main local inflammatory mediators : by COX2 inhibition effect, it may inhibit prostaglandins, 12 prostacyclins, 12 histamine, 38 bradykinins 6,33,39 and NO 31 and (5) Antiangiogenic effect : by COX‐2 inhibition effect, it would negatively modulate vascular endothelial growth factor (VEGF), 40,42 basic fibroblast growth factor (bFGF), 40,42 CCL2, 27 HGF, 27 extracellular signal‐regulated kinase 2 (ERK2), 40 mitogen‐activated protein kinase (MAPK), 40 cyclin‐dependent kinase 1/2 (CDK 1/2), 40 checkpoint kinase 1 (CHK1), 40 cyclin A, 40 via Apelin/G protein‐coupled receptor (APJ) 40 and, by COX‐independent effect, NaIHS would inhibit hypoxia inducible factor‐1 alpha (HIF‐1α) 37 and HIF‐2α 43 . .…”
Section: Potential Therapeutic Effects Of Naihs In Pneumonia and Card...mentioning
confidence: 99%
“…In general, EOs are isolated from the aqueous phase using a physical technique resulting in no or little significant changes in their chemical profile. To generate these aromatic oily liquids, various plant segments such as seeds, leaves, flowers, peels, buds, and others are employed, and various extraction procedures are used (Thitinarongwate et al., 2022).…”
Section: Introductionmentioning
confidence: 99%